Teaching the fundamentals of information systems management in health care: lecture and practical training for students of medical informatics - Knaup-Gregori, Petra; Haux, Reinhold; Häber, Anke Erika; Lagemann, Anita; Leiner, Florian (International journal of medical informatics, 1998)
For the management of information systems in health care, it is important that projects are systematically planned and carried out. This is a major task for medical informatics professionals which should be taught in a medical informatics curriculum. In the respective lecture in the Heidelberg/Heilbronn medical informatics curriculum, we teach fundamentals of the management of information systems and of projects. The examples of the lecture are taken from hospital information systems. Furthermore, we have developed a 5-step method for the systematic, goal-oriented planning of projects. The lecture is complemented by a comprehensive practical training, so that the methods taught can be applied to a particular, relevant problem of the Heidelberg University Hospital.